2022
DOI: 10.1530/etj-21-0119
|View full text |Cite
|
Sign up to set email alerts
|

Central hypothyroidism related to antipsychotic and antidepressant medications: an observational study and literature review

Abstract: Objective: To investigate the final diagnosis and clinical outcome of patients referred to endocrinology in our district general hospital with biochemical isolated central hypothyroidism, and whether there is an association between this biochemical picture and treatment with antidepressant and antipsychotic medications. Methods: We performed a retrospective observational study of patients referred to endocrinology with unexplained biochemical isolated central hypothyroidism over a 5 year period. Results: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Our initial research took place as a single-centre retrospective study. 5 and supported our suspicion that isolated CeH, in the absence of any other pituitary hormone dysfunction, did not appear to be associated with any significant pituitary pathology. Our study also demonstrated a convincing relationship between antidepressant and antipsychotic medications and biochemical CeH.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our initial research took place as a single-centre retrospective study. 5 and supported our suspicion that isolated CeH, in the absence of any other pituitary hormone dysfunction, did not appear to be associated with any significant pituitary pathology. Our study also demonstrated a convincing relationship between antidepressant and antipsychotic medications and biochemical CeH.…”
Section: Introductionsupporting
confidence: 83%
“…Our initial research took place as a single‐centre retrospective study 5 . and supported our suspicion that isolated CeH, in the absence of any other pituitary hormone dysfunction, did not appear to be associated with any significant pituitary pathology.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Indeed, many drugs, such as bexarotene ( 97 ), mitotane ( 98 ) and immune checkpoint inhibitors ( 99 ) may alter the thyrotropic cell activity of TSH production or release determining, in general, permanent CH ( 96 ). Other drugs, like glucocorticoids, dopamine/dopamine-agonists, somatostatin analogues, metformin ( 100 ) as well as some antipsychotic and antidepressant medications ( 101 ), may exert a mild suppressive effect on TSH release without appreciably affecting circulating fT4 levels and hence without a real clinical significance ( 96 ). Finally, certain antiepileptic medications, including carbamazepine, oxcarbamazepine, valproic acid and phenytoin along with salsalate may determine falsely low levels of fT4 (secondary to pre-analytical variability due to sample dilution) and normal TSH levels in clinically euthyroid patients, mimicking the biochemical picture of ICH ( 96 , 102 , 103 ).…”
Section: Isolated Central Hypothyroidismmentioning
confidence: 99%